2009
DOI: 10.1111/j.1471-6402.2009.01505.x
|View full text |Cite
|
Sign up to set email alerts
|

ASIAN AMERICAN WOMEN's RETROSPECTIVE REPORTS OF THEIR SEXUAL SOCIALIZATION

Abstract: This study used qualitative research methods to investigate the sexual socialization experiences of young Asian American women, a group often overlooked in psychological research on sexuality. Focus group interviews were conducted with 30 ethnically diverse young Asian American women to explore their perceptions and interpretations of the direct and indirect sexual communication they received from parents during adolescence. Interviews were analyzed using open and focused coding techniques based on principles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 58 publications
(78 reference statements)
2
17
0
Order By: Relevance
“…Discussions of sexuality, sex, and sexual expression were discouraged and avoided in public and even regarded in Asian-American homes as a taboo subject (Hahm et al, 2006;Kao, 2006). This contributes to Asian-American adolescents having less parent-initiated sex education, and making adolescents reluctant and uncomfortable in discussing sexuality and sexual information with their parents (Kao, 2006;Kim, 2009). In evaluating the relationship between traditional family support and condom use, a recent study revealed that there was no relationship between these two variables among Asian-American adolescents while the family support was strongly related to condom use in African American adolescents and white adolescents (Gillmore, Chen, Hass, Kopak, & Robillard, 2011).…”
Section: Family Centered Cultural Valuesmentioning
confidence: 93%
See 3 more Smart Citations
“…Discussions of sexuality, sex, and sexual expression were discouraged and avoided in public and even regarded in Asian-American homes as a taboo subject (Hahm et al, 2006;Kao, 2006). This contributes to Asian-American adolescents having less parent-initiated sex education, and making adolescents reluctant and uncomfortable in discussing sexuality and sexual information with their parents (Kao, 2006;Kim, 2009). In evaluating the relationship between traditional family support and condom use, a recent study revealed that there was no relationship between these two variables among Asian-American adolescents while the family support was strongly related to condom use in African American adolescents and white adolescents (Gillmore, Chen, Hass, Kopak, & Robillard, 2011).…”
Section: Family Centered Cultural Valuesmentioning
confidence: 93%
“…Adolescents have also reported that they would prefer to receive sexual education from their parents rather than other sources (Somers & Surmann, 2004). However, some studies reported an opposite finding: most adolescents, including Asian-American adolescents, perceived their parents to be reluctant to speak about sex and sexuality (Kao, 2006;Kao et al, 2011;Kim, 2009). The reluctance may be strongly related to the Asian culture that emphasizes family values, obedience to parents, and sexual innocence until marriage (Kao, 2006;Kao et al, 2011;Kim, 2009;Okazaki, 2002).…”
Section: Parental Relationshipmentioning
confidence: 94%
See 2 more Smart Citations
“…During adolescence, parents play an important role in helping their children to recognize what is appropriate behavior and to cultivate a set of moral values (Strouse & Fabes, 1985). Parents may influence their children"s sexual development through direct communication (Fox & Inazu, 1980;Holtzman & Rubinson, 1995), nonverbal behavior (Kim, 2009), and emotional qualities of the relationship (Jaccard, Dittus, & Gordon, 1996). When parents become involved in sexuality education for children, this involvement has the potential to postpone or forestall children"s sexual activity, and promote safer sexual practices (e.g., Dilorio, Bluhar, & Belcher, 2003; Fox & Inazu, 1980;Hutchinson, 2002).…”
mentioning
confidence: 99%